Self-harm in the context of borderline personality disorder - Reichl, Corinna; Kaess, Michael (Current opinion in psychology, 2021)
The present article gives a selective overview of recent studies on the role of nonsuicidal self-injury (NSSI) and suicidal behavior in the context of borderline personality disorder (BPD). Previous research found self-harming behavior, particularly NSSI, to constitute an easily accessible marker in the early detection of individuals at risk of development of BPD. The review further summarizes studies that investigated inter-relations between BPD features and self-harming behavior over time. Mainly, affective instability has been shown to play a role in the maintenance of NSSI and the increased risk of suicidal behavior among individuals with BPD. Finally, results about the effectiveness of treatment programs on the reduction of self-harming behavior among individuals with BPD are presented.
Gesehen am 25.05.2021